Maize Infestation of Fall Armyworm (Lepidoptera: Noctuidae) Within Agro-Ecological Zones of Togo and Ghana in West Africa 3 Yr After Its Invasion - Koffi, D.; Agboka, K.; Adenka, D.K.; Osae, M.; Tounou, A.K.; Adjevi, M.K.A.; Fening, K.O.; Meagher, R.L.J. (Environmental Entomology, 2020)
The fall armyworm Spodoptera frugiperda (J. E. Smith) invaded several West African countries in 2016 causing severe injury to maize plants and economic damage. This study assesses variations in the occurrence of this species in different Agro-Ecological Zones (AEZs) in Togo and Ghana during the 3 yr following its discovery. The surveys were conducted on 120 farms in Togo and 94 farms in Ghana by collecting larvae from 200 maize plants per hectare. Infestation levels were 68.46% in 2016, 55.82% in 2017, and 17.76% in 2018. The number of larvae recorded per hectare and infestation levels were higher in Togo than in Ghana. The lowest number of collected larvae and infestation levels of S. frugiperda were in 2018, compared to the other 2 yr. Larvae per hectare and the infestation level varied regionally inside the two countries. The southern part of Togo (AEZ five) contained higher numbers of larvae and higher infestation levels during the 2 yr following the invasion of the pest. We concluded that infestation levels of S. frugiperda are much lower in 2018 than the two previous years and it is therefore necessary to determine the factors that affect the population dynamics of S. frugiperda in the field, which is a perquisite for developing management interventions.
Research Article
Keywords: fall armyworm; Agro-Ecological Zone; distribution pattern; infestation; maize